Study on role of fibular graft in non-union and complex fractures of long bone - Singh, Anoop; Kapoor, Raj; Verma, Manoj; Saraogi, Praveen Raj (Asian Journal of Medical Sciences, 2023)
Background: Road traffic injuries are the seventh most common cause of long bone fractures. Following high velocity limb trauma, the defects in the long bone are usually associated with appreciable soft-tissue losses. These open long bone injuries always require multidisciplinary managements to reconstruct the composite defects of bone and soft tissue. Aims and Objectives: The aim of the study was to find out radiological and clinical outcome, complications, and union time in complex and non-union fractures of long bone managed by fibular graft. Materials and Methods: Out of 50 cases, 40 cases were of complex fractures and ten cases were of non-union. We used Fibular strut grafts in reconstruction of bone defects and soft tissue injury. Results: Thirty (60.0%) had excellent functional outcome, 10 (20.0%) had good, 6 (12.0%) had satisfactory, and 4 (8.0%) patients had poor outcome. Main complications were non-union 2 cases and 3 cases of superficial wound infection, which subsided by wound dressing and intravenous antibiotic treatment. Conclusion: Free fibular grafting has been proven to be an ideal choice in the management of large segmental bone defects as well as in situations of biological failure of bone healing.